Cloning and characterization of short‐chain N ‐acyl homoserine lactone‐producing Enterobacter asburiae strain L1 from lettuce leaves - Lau, Yin Yin; How, Kah Yan; Yin, Wai Fong; Chan, Kok Gan (Wiley Open Access, 2018)
In gram-negative bacteria, bacterial communication or quorum sensing (QS) is achieved using common signaling molecules known as N-acyl homoserine lactones (AHL). We have previously reported the genome of AHL-producing bacterium, Enterobacter asburiae strain L1. In silico analysis of the strain L1 genome revealed the presence of a pair of luxI/R genes responsible for AHL-type QS, designated as easIR. In this work, the 639 bp luxI homolog, encoding 212 amino acids, have been cloned and overexpressed in Escherichia coli BL21 (DE3)pLysS. The purified protein (~25 kDa) shares high similarity to several members of the LuxI family among different E asburiae strains. Our findings showed that the heterologously expressed EasI protein has activated violacein production by AHL biosensor Chromobacterium violaceum CV026 as the wild-type E. asburiae. The mass spectrometry analysis showed the production of N-butanoyl homoserine lactone and N–hexanoyl homoserine lactone from induced E. coli harboring the recombinant EasI, suggesting that EasI is a functional AHL synthase. E. asburiae strain L1 was also shown to possess biofilm-forming characteristic activity using crystal violet binding assay. This is the first report on cloning and characterization of the luxI homolog from E. asburiae.